PRELIMINARY ANALYSIS OF CORE TEMPERATURE DISTRIBUTION OF EXPERIMENTAL POWER REACTOR USING RELAP5 - Andi Sofrany Ekariansyah; Surip Widodo; Hendro Tjahjono; Susyadi Susyadi; Puradwi Ismu Wahyono; Anwar Budianto (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2018)
High Temperature Gas Cooled Reactor (HTGR) is a high temperature reactor type having nuclear fuels formed by small particles containing uranium in the core. One of HTGR designs is Pebble Bed Reactor (PBR), which utilizes helium gas flowing between pebble fuels in the core. The PBR is also the similar reactor being developed by Indonesia National Nuclear Energy Agency (BATAN) under the name of the Reaktor Daya Eksperimental (RDE) or Experimental Power Reactor (EPR) started in 2015. One important step of the EPR program is the completion of the detail design document of EPR, which should be submitted to the regulatory body at the end of 2018. The purpose of this research is to present preliminary results in the core temperature distribution in the EPR using the RELAP5/SCDAP/Mod3.4 to be complemented in the detail design document. Methodology of the calculation is by modelling the core section of the EPR design according to the determined procedures. The EPR core section consisting of the pebble bed, outlet channels, and hot gas plenum have been modelled to be simulated with 10 MWt. It shows that the core temperature distribution under assumed model of 4 core zones is below the limiting pebble temperature of 1,620 °C with the highest pebble temperature of 1,477.0 °C. The results are still preliminary and requires further researches by considering other factors such as more representative radial and axial power distribution, decrease of core mass flow, and heat loss to the reactor pressure vessel.Keywords: Pebble bed, core temperature, EPR, RELAP5 ANALISIS AWAL DISTRIBUSI TEMPERATUR TERAS REAKTOR DAYA EKSPERIMENTAL MENGGUNAKAN RELAP5. High Temperature Gas Cooled Reactor (HTGR) adalah reaktor tipe temperatur tinggi yang memiliki bahan bakar nukir dalam bentuk bola-bola kecil yang mengandung uranium. Salah satu desain HTGR adalah reaktor pebble bed (Pebble bed reactor/PBR) yang memanfaatkan gas helium sebagai pendingin yang mengalir di celah-celah bahan bakar bola di dalam teras. PBR juga merupakan tipe reaktor yang sedang dikembangkan oleh BATAN dengan nama reaktor daya eksperimental (RDE) yang dimulai pada 2015. Salah satu tahapan penting dalam program RDE adalah penyelesaian dokumen desain rinci yang harus dikirimkan ke badan pengawas pada akhir 2018. Tujuan penelitian adalah untuk menyajikan hasil-hasil awal pada distribusi temperatur di teras RDE menggunakan RELAP5/SCDAP/Mod3.4 sehingga dapat melengkapi isi dokumen desain rinci. Metode perhitungan adalah dengan memodelkan bagian teras RDE sesuai hasil penelitian sebelumnya. Bagian teras RDE yang dimodelkan terdiri dari pebble bed, kanal luaran, dan plenum gas bawah yang disimulasikan pada daya 10 MWt. Hasil simulasi menunjukkan bahwa distribusi temperatur teras dengan asumsi pembagian 4 zona teras mendapatkan temperatur tertinggi sebesar 1477 °C yang masih di bawah batasan temperatur di bola bahan bakar yaitu 1620 °C. Hasil yang diperoleh masih estimasi awal dan membutuhkan penelitian lebih lanjut dengan mempertimbangkan faktor-faktor lainnya seperti distribusi daya aksial dan radian yang lebih representatif, pengurangan aliran teras, dan kehilangan panas teras yang diserap oleh bejana reaktor.Kata kunci: Pebble bed, temperatur teras, RDE, RELAP5